THE ABILITY OF THE SECOND YEAR STUDENTS OF SMP KATOLIK TRISAKTI 1 MEDAN IN USING VERB BE - Zebua, Berkat Aman; Lumban Raja, Viator; Ginting, Fiber Yun A (Kairos English Language Teaching Journal, 2020)
Grammar is a description of certain organizing aspects of a written particular language. One of the grammar topic is verb BE. Verb BE is important in English Grammar, BE is the one of the elementary and earlier phases of subject verb agreement. The purpose of this research was to describe the ability of the second year students in using verb BE. This research was descriptive research. The population of this research was the second year students were take as a sample, and totals 40 students. The instrument of collecting data was a test concerning verb BE. The try out test was done in order to know the validity, reliability, item difficulty and power discrimination of test items. The result showed that 9 students (22.50%) belong to high category, 28 students (70%) to moderate category, and 3 students (7.50%) to low category. The mean score was 65.10 it was only 30% of the total students who can do the test well with 12 students who get score above 70. It means that the second year students at SMP Katolik Trisakti 1 Medan are not yet able to use the verb BE. Some students do not understand the rule of verb BE, how to apply it in sentences because there were a lot of rules and exception in verb BE. The students also had some difficulties in using verb BE. The students did not know the form of some tenses such as simple present tense, simple past tense etc. Based on the total incorrect answers made by the students in each tense was 349. The percentage studentsÂ mistakes made using verb Be in Present Tense was 28.57%, and the percentage students mistakes made using verb Be in Past Tense was 11.46%, So the most mistakes made by the second year students in using verb Be was in present tense, the percentage was 28.57%. Thus, the students are suggested to study more the lesson of verb BE and to do the assignments well. The teacher also expected to give explanation of the materials of verb BE crearly